WASTE MANAGEMENT BASED ON CIRCULARITY IN PAHLAWAN VILLAGE, TANJUNG TIRAM SUB-DISTRICT - Faried, Annisa Ilmi; Sembiring, Rahmad; Wardhani, Neng Sri (Proceeding International Seminar of Islamic Studies, 2023)
The problem of waste is multidimensional, so it must be handled regularly. Waste reduction requires a cooperative effort from all parties involved. Accomplishing the Village Sustainable Development Goals (SDGs) in 2030 is one of the cross-sectoral challenges and problems that the Hero Village is trying to solve. This paper aims to look at circularity-based waste management and provide insight on how green recovery stimulus can be achieved. Doing this is to control the negative environmental, economic, social, and rural effects that threaten villages, and to reap the benefits that come from doing so. One reason is because the funds allocated by the government are insufficient for rural waste management. Even for today's trash.